2013
DOI: 10.1093/jnci/djt151
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Prostate Cancer on Autopsy: Cross-Sectional Study on Unscreened Caucasian and Asian Men

Abstract: PCa is found on autopsy in a similar proportion of Russian and Japanese men. More than 50% of cancers in ASI and nearly 25% of cancers in CAU men have a GS of 7 or greater. Our results suggest that the definition of clinically insignificant PCa might be worth re-examining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(168 citation statements)
references
References 39 publications
5
154
5
Order By: Relevance
“…This figure is likely to be an underestimation since many histological cases of malignant transformation do not advance to clinical disease. Autopsy evaluation of 320 men without apparent clinical history of prostate cancer, detected evidences of malignant transformations in 40% of cases older than 60 years (Zlotta et al, 2013). Our results are in accordance with previous reports that older patients who were diagnosed with prostate cancer have shorter survival probably due to comorbidities deteriorating health status (Holmberg et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…This figure is likely to be an underestimation since many histological cases of malignant transformation do not advance to clinical disease. Autopsy evaluation of 320 men without apparent clinical history of prostate cancer, detected evidences of malignant transformations in 40% of cases older than 60 years (Zlotta et al, 2013). Our results are in accordance with previous reports that older patients who were diagnosed with prostate cancer have shorter survival probably due to comorbidities deteriorating health status (Holmberg et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…A number of epidemiological studies have also reported on the incidence of multiple primary tumors within the same or neighboring organs, with potentially important insights (10)(11)(12)(13)(14)(15)(16)(17). Notably, premalignant lesions are usually excluded from cancer statistics so that real frequencies of MP lesions are likely to be significantly underestimated, a conclusion supported by the staggering numbers of premalignant and malignant lesions that are discovered by autopsy studies of individuals with other causes of death (30%-40% of cases) (18)(19)(20)(21).…”
Section: The Clinical Problemmentioning
confidence: 99%
“…Use of the prostate-specific antigen (PSA) test in PCa screening is controversial, due to uncertainty surrounding its benefits and risks (2); the PSA test can identify asymptomatic, indolent tumors, leading to unnecessary treatments and significant side effects associated with these treatments (1,3). The prevalence of clinically indolent tumors has been estimated to range from 30 to 70% in men aged >60 years (4,5). Therefore, a reliable method for distinguishing between indolent and aggressive PCa is urgently required.…”
Section: Introductionmentioning
confidence: 99%